Essential oil composition of bark and leaves of Cinammoum verum Bertch. & Presl from Mizoram, North East India. Issue 6 (1st November 2016) - Malsawmtluangi, Lydia; Nautiyal, Bhagwati P.; Hazarika, Tridip; Chauhan, Rajendra S.; Tava, Aldo
Abstract: Stem bark and leaf essential oil of Cinammoum verum Bertch. & Presl in Mizoram India was extracted and analyzed for composition. On hydro distillation, 0.87% and 2.13% (w/w) essential oil was yielded from leaves and bark, respectively. Overall, twenty compounds were identified in bark and twenty-one in leaf oil using GC-FID and GC–MS analysis. The major components of bark essential oil were methyl cinnamate (81.87%), linalool (3.90%) and αpinene (2.41%) whereas; linalool (67.60%), methyl cinnamate (17.32%) and αpinene (2.74%) were major components of leaf volatile oil. On comparison of our results with earlier studies on various species of Cinnamon as well as C. verum, marked variations exist not only on identity of compounds but also in their percent share in the composition of essential oil. Our observation indicates possibility of Cinnamic aldehyde and eugenol derivatives rich chemotype (Mizoram) of C. verum . Besides, factors which may affect oil composition are also discussed.